An integrative model of autonomous agent teammate-likeness. (4th May 2018) - Wynne, Kevin T.; Lyons, Joseph B.
ABSTRACT: Advancements in autonomy are beginning to allow humans to partner with machines in order to accomplish work tasks in various settings. As human–agent teaming (HAT) becomes more prevalent as a research topic, the need to understand humans' psychological perceptions of the machine partner is increasingly important, especially in terms of its perceived role, which may ultimately impact trust and team effectiveness. Specifically, it remains unclear how humans perceive intelligent agents and how consistent these perceptions are with existing taxonomies found in the psychology of teams. The present paper presents a definition of the construct of autonomous agent teammate-likeness (AAT) and a conceptual model of its components, reviews related concepts and germane research and proffers a number of propositions to guide future research. The goal is to contribute to the nascent literature on HAT by establishing a theoretical foundation for the AAT construct, upon which researchers can advance research on HAT.